2023
DOI: 10.1177/11795549231156692
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Extranodal NK/T-Cell Lymphoma, Nasal Type, Compared with Nasal Diffuse Large B-cell Lymphoma

Abstract: Background: Extranodal NK/T-cell lymphoma, nasal type (ENKL), is an aggressive tumour with poor prognosis. Its early diagnosis may improve the prognosis of patients; however, it is often overlooked in many cases and misdiagnosed as an inflammatory sinus disease during its initial stage. Identifying the clinical characteristics of ENKL may aid otorhinolaryngologists in indicating cases early for a pathologic examination. In this study, we aimed to investigate the clinical characteristics of ENKL compared with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 17 publications
0
7
2
Order By: Relevance
“…2,3 As in other studies, ENKL caused more nasal symptoms than DLBCL, probably because it occurred in the nasal cavity (p < 0.05). [2][3][4] However, both DLBCL and ENKL exhibit similar symptoms to chronic sinusitis, making it impossible to differentiate based on symptoms. [1][2][3][4][5] In this study, ENKL demonstrated a smaller size than DLBCL, because it occurred in the nasal cavity and symptoms developed quickly (p < 0.05).…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…2,3 As in other studies, ENKL caused more nasal symptoms than DLBCL, probably because it occurred in the nasal cavity (p < 0.05). [2][3][4] However, both DLBCL and ENKL exhibit similar symptoms to chronic sinusitis, making it impossible to differentiate based on symptoms. [1][2][3][4][5] In this study, ENKL demonstrated a smaller size than DLBCL, because it occurred in the nasal cavity and symptoms developed quickly (p < 0.05).…”
Section: Discussionmentioning
confidence: 52%
“…DLBCL is the most common lymphoma arising in the nasal cavity and paranasal sinuses. [1][2][3][4][5][6] However, the incidence of ENKL was higher in this study, probably because only Asians were included. 6 ENKL occurred at a younger age than DLBCL (p < 0.05).…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations